The role of job and personal resources in alleviating dentists’ emotional dissonance in dental clinics of Hyderabad: a cross sectional study - Priya, S. Vishnu; Anjum, M. Shakeel; Hariprasad, G.; Sravya, T.; Pravalika, T. Sai; Jyothi, M. (International Journal Of Community Medicine And Public Health, 2020)
Background: ‘Emotional dissonance’ (the discrepancy between the felt and expressed emotions) could occur in dentistry due to the challenge of pacifying patients irrespective of the dentist’s state of mind and could influence their performance. The presence of certain factors could minimize this though. Our aim was to examine the role of ‘optimism’ and ‘relation with colleagues’ in buffering the effect of emotional dissonance on the performance of dentists. Methods: Emotional dissonance’ was evaluated among 390 dentists of Hyderabad using Zapf scale; ‘optimism’ using 3-items adapted from ‘The Life Orientation Test (LOT)’, ‘relation with colleagues’ assessed with a self-constructed 4-item scale and the ‘performance of a dentist’ using 6 items picked from Goodman scale. Regression analysis was done using SPSS 24, to predict the influence of ‘optimism’ and ‘relation with colleagues’ on the ‘performance’ of dentists in dissonance. Results: Emotional dissonance was found to be negatively related to dentists’ performance. ‘Optimism’ (p=0.018) and ‘relation with colleagues’ (p=0.039) significantly predicted their performance when under dissonance, but in the negative direction. Conclusions: The results necessitate the need to identify various resources to handle dissonance owing to its intensity found in the present study.